PENGARUH PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN PAI DI UPT SD NEGERI 347 GRESIK - Kusfa Hariani Putri; Anwar Sa’dullah; Zuhkhriyan Zakaria (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
This research explain how online learning influnce toward studying result. Learning outcomes students subject of islamic education learning in SD Negeri 347 Gresik when pandemic situation and before pandemic situation there are two value, that is skill value and knowladge value. Kowladge value before pandemic more high when pandemic situation, and skill value before pandemic is more high when pandemic situation. Daring learning in SD Negeri 347 Gresik isn’t influence toward learning outcomes. This research use quantitative research with SPSS aid. The conclusion of this research is online learning isn’t influence toward studying result. Keyword: Online learning, Pandemic Covid-19, Learning outcome